Desenvolvimento de protocolo de caracterização da pele dos dedos por dermatoscopia e fotografia. - Rossilho Casale, Andresa; Calissi Petri, Tatiana; Telles, Juliana Rhein; Jerônimo da Costa, Jéssica Candido; da Silva, Ronaldo Luis; Callil Voos, Mariana; Alves Vale, Fernando; Aparecida Caromano, Fátima (Fisioterapia Brasil, 2025)
Introduction: Dermoscopy is a technique for collecting images of the skin for simple assessment and can be used by various health professionals. Objective: This study aimed to develop a method for collecting images by dermatoscopy and photography and a protocol to characterize the skin of the fingertips. Methods: Descriptive, observational, psychometric and prospective study, divided into five phases: 1. Development of the protocol and its manual; 2. Peer-to-peer construct analysis; 3. Usability analysis; 4. Reliability analysis and characterization of the sample (two groups with 50 individuals, aged 20-30 and 60-80 years, of which 25 perform work activities); and 5. Peer-to-peer construct analysis and usability analysis by university students in the health area. Results: Data from the reliability analysis were good to excellent. Older participants showed more changes in all protocol variables, except thickness. People with manual activities showed more changes in hydration, thickness and elementary lesions. The younger ones, without manual activities, had a lower score and the older ones with manual activities had a higher score. Conclusion: The protocol developed allows permanent recording, meeting a demand in the literature and allowed the observation of variations in the skin quality of different populations.